2018
DOI: 10.1186/s12909-018-1305-0
|View full text |Cite
|
Sign up to set email alerts
|

Pure PBL, Hybrid PBL and Lecturing: which one is more effective in developing cognitive skills of undergraduate students in pediatric nursing course?

Abstract: BackgroundNursing education in Iran has conventionally focused on lecture-based strategies. Improvements in teaching and learning over the years have led to an expansion of the pedagogies available to educators. Likewise, there has been a suggestion for a move toward more learner-centered teaching strategies and pedagogies that can result in improvement in learning. This study was undertaken to investigate the effects of Problem-Based Learning in developing cognitive skills in learning Pediatric Nursing among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 67 publications
1
27
0
3
Order By: Relevance
“…In addition, the facilitator prompts reflection of group process and group outcomes. The facilitator may also be considered a coach or a guide who provides feedback and encouragement ( Salari, Roozbehi, Zarifi & Tarmizi, 2018 ).…”
Section: Pblmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the facilitator prompts reflection of group process and group outcomes. The facilitator may also be considered a coach or a guide who provides feedback and encouragement ( Salari, Roozbehi, Zarifi & Tarmizi, 2018 ).…”
Section: Pblmentioning
confidence: 99%
“…Recently, Zhou (2018) conducted a study of the influence of PBL on critical thinking in nursing students and discovered that PBL improved the analysis and interpretation elements of critical thinking. Likewise, Salari et al, (2018) also studied the effects of PBL on nursing student development of higher order cognition. Their results aligned with other studies, which demonstrated that PBL was more effective than traditional lectures to engage students in application, analysis, evaluation, and synthesis.…”
Section: Pblmentioning
confidence: 99%
“…Estudo realizado no Irã revelou que acadêmicos de enfermagem submetidos à PBL apresentaram melhores níveis de desempenho geral durante as atividades de aprendizagem, com um menor esforço mental que os alunos do método convencional. Além disso, o método ativo foi relacionado ao aumento da carga cognitiva dos alunos e a retenção do conhecimento a longo prazo (Salari et al, 2018).…”
Section: Discussionunclassified
“…O desempenho a longo prazo dos alunos de enfermagem submetidas a PBL mostrou-se superior aos do método convencional (Salari, Roozbehi, Zarifi, & Tarmizi, 2018). No entanto, um estudo revelou que alunos que seguiam a metodologia PBL mostraram-se mais estressados durante a maior parte do programa de graduação, em comparação aos alunos que utilizavam o método de aprendizagem baseado em aulas expositivas (Wardley et al, 2016).…”
Section: Introductionunclassified
“…In a study with 95 nursing students randomly assigned to traditional lectures, lectures plus problem-based learning and solely problem-based learning, those with a component of problem-based learning did significantly better, p ¼ 0.001, on testing immediately after and after weeks of delay. 9 Another creative adjunct to standard anatomy lectures involved the addition of live narrated interactive video streaming of live surgical procedures. In this nonrandomized study, 138 medical students performed significantly better on clinically related multiplechoice questions, p < 0.05, relative to fellow dental students who participated in traditional lectures alone.…”
Section: Discussionmentioning
confidence: 99%